The authorship problem in theatrical collective production. An analysis on the play 3x3 by Manojo de Calles from Tucumán (Anclajes, 2011)
The history of Western theatre provides several examples of authorship disputes among producers of theatrical works. The present paper is aimed at analyzing some arguments derived from the linkage between theatre and literature, particularly, the problematic relation between theatre producers and playwrights. To do so, we have selected the play 3x3 by the school Manojo de Calles from Tucumán. Such a production will allow us to review Enrique Buenaventura and Jacqueline Vidal’s Nuevo Teatro writings from a post-structuralist perspective supported by Jacques Derrida’s readings on Antonin Artaud’s “Teatro de la Crueldad.”
Keywords: playwright; collective production; Tucumán; argentine theatre